A Kepemimpinan Dan Budaya Korporat Untuk Meningkatkan Kinerja Karyawan: Kinerja Karyawan - Fatmawati, Lisa Nur; Solin, Raslina (Economic Reviews Journal, 2024)
The offenders are intimately tied to any violations or failures on the part of the organization to carry out its obligations. The performance of an organization is significantly influenced by its human resource management. incorporating into company performance This study looked at the relationship between motivation, corporate culture, and employee performance. The test results demonstrate that motivation, corporate culture, and leadership all have significant effects simultaneously. Employee performance is partially influenced by management and corporate culture, although motivation has little to no impact. The organizational culture and management style both contribute to employee work satisfaction. Employee performance benefits directly from management style and organizational culture as well as indirectly from job happiness. According to this study, corporate culture has the biggest influence on worker performance and job happiness.